2016
DOI: 10.26719/2016.22.8.603
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of serum levels and significance of soluable CD40 ligand in screening patients with hepatitis C virus-related hepatocellular carcinoma

Abstract: The study's objective was to evaluate the clinical significance of sCD40L in HCV-associated hepatocellular carcinoma (HCV-HCC) patients. Sera concentration of circulating sCD40L and IL-10 were assayed using ELISA in 30 HCVpositive patients with HCC, 30 HCV-positive patients with liver cirrhosis and 30 age-matched healthy volunteers with negative anti-HCV-Ab as a control group. Serum sCD40Lshowed statistically-significant high levels in HCV-HCC patients compared to HCV-cirrhotic patients and normal controls (P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
(37 reference statements)
0
8
0
Order By: Relevance
“…The characteristics of the studies included in the meta-analysis are shown in Table 1 . Three studies were reported from Japan [ 6 , 11 , 12 ], one from Korea [ 1 ], one from Taiwan [ 9 ], one from China [ 13 ], and three from Egypt [ 14 - 16 ]. Altogether the studies included 373 HCC patients, 215 healthy controls, 132 cirrhotic patients and 92 patients with hepatitis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The characteristics of the studies included in the meta-analysis are shown in Table 1 . Three studies were reported from Japan [ 6 , 11 , 12 ], one from Korea [ 1 ], one from Taiwan [ 9 ], one from China [ 13 ], and three from Egypt [ 14 - 16 ]. Altogether the studies included 373 HCC patients, 215 healthy controls, 132 cirrhotic patients and 92 patients with hepatitis.…”
Section: Resultsmentioning
confidence: 99%
“…IL-10 is known as a pleiotropic cytokine with dual roles in the immune system, including immune suppression and immune stimulation [ 17 ]. Many studies have reported that serum IL-10 levels were higher in the HCC patients than in the healthy controls [ 1 , 6 , 9 , 11 - 16 , 18 ] and that a higher IL-10 level was associated with worse prognosis [ 19 ]. Increased levels of IL-10 have been described as a negative prognostic indicator for survival in patients with various types of cancer [ 9 , 18 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have evaluated the use of protein biomarkers in African populations; with some aiming at the discovery of novel protein biomarkers [184,185,186,187,188,189,190,191,192,193,194,195,196,197,198,199,200]. A study by Adeola, et al [15] identified 73 urinary proteins as potential biomarkers for prostate cancer in the South African population.…”
Section: Component Of Liquid Biopsymentioning
confidence: 99%
“…Patients with chronic hepatitis C virus infection[ 76 ], cirrhosis[ 77 ], and non-alcoholic fatty liver disease have been shown to exhibit higher circulating sCD40L levels than control subjects[ 78 ]. Furthermore, high circulating sCD40L levels are associated with a poor prognosis in HCC patients[ 79 ].…”
Section: Biomarkersmentioning
confidence: 99%